2014
DOI: 10.1039/c3ce42663g
|View full text |Cite
|
Sign up to set email alerts
|

Defect reduction in semipolar {101̄3̄} GaN grown on m-sapphire via two-step nanoepitaxial lateral overgrowth

Abstract: A method to obtain high quality semipolar {101̄3̄} GaN grown on m-plane sapphire is presented. This method is similar to two-step nanoepitaxial lateral overgrowth (2S-NELOG) by combining a TiN interlayer and self-assembled SiO2 nanospheres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…[17][18][19][20][21][22] In order to circumvent the issue, several technologies, such as buffer layer, epitaxial lateral overgrowth, pattern design of the Si substrates, etc., need to be used. [44][45][46][47][48][49][50][51] These technologies can reduce dislocation density and release the stress to some extent, and eventually benefit the growth of high-quality Al films on Si substrates. [44][45][46][47][48][49][50][51] Therefore, these pieces of evidence show the higher crystalline quality of Al epitaxial film grown in this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][22] In order to circumvent the issue, several technologies, such as buffer layer, epitaxial lateral overgrowth, pattern design of the Si substrates, etc., need to be used. [44][45][46][47][48][49][50][51] These technologies can reduce dislocation density and release the stress to some extent, and eventually benefit the growth of high-quality Al films on Si substrates. [44][45][46][47][48][49][50][51] Therefore, these pieces of evidence show the higher crystalline quality of Al epitaxial film grown in this work.…”
Section: Resultsmentioning
confidence: 99%
“…[44][45][46][47][48][49][50][51] These technologies can reduce dislocation density and release the stress to some extent, and eventually benefit the growth of high-quality Al films on Si substrates. [44][45][46][47][48][49][50][51] Therefore, these pieces of evidence show the higher crystalline quality of Al epitaxial film grown in this work. This achievement of higher quality Al epitaxial films mainly may be ascribed to two aspects.…”
Section: Resultsmentioning
confidence: 99%
“…N-polar (101 ¯3 ¯) GaN epilayers have been mainly obtained. 12,[17][18][19][20][21] Jo et al reported (101 ¯3 ¯) AlN growth on the (101 ¯0) sapphire substrate without nitridation by MOCVD. 31 They pointed out that nitridation is a key factor in controlling the crystal orientations of semipolar AlN grown on an m-plane sapphire substrate.…”
Section: Discussion and Eds Results Around An Idbmentioning
confidence: 99%
“…Research works concerning the heteroepitaxial growth of semipolar {101 ¯3} epilayers on m-plane (101 ¯0) sapphire substrates have been reported. 12,[17][18][19][20][21][22][23][24][25] Based on the reports, it is possible to grow both N-polar (101 ¯3 ¯) and metal-polar (101 ¯3) III-nitride semipolar planes. (101 ¯3 ¯) GaN epilayers have been mainly grown by hydride vapor phase epitaxy (HVPE) and metalorganic chemical vapor deposition (MOCVD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation